2013
DOI: 10.1089/scd.2012.0376
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Tip/Stalk-Like and Phalanx-Like Endothelial Cells from Embryonic Stem Cells

Abstract: Endothelial cells (EC) generated in vitro from stem cells are desirable for their potential in a variety of in vitro models and cell-based therapeutic approaches; however, EC can take on a number of functionally and phenotypically distinct specializations. Here, we show the generation of functionally distinct EC subpopulations, including (1) the pro-angiogenic migrating tip-like and proliferative stalk-like EC, and (2) the less migratory cobblestone-shaped phalanx-like EC. Both embryonic stem cell (ESC)-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
2
28
0
1
Order By: Relevance
“…Moreover, the profile of cytokines secreted by the sprouting cells was very similar to that observed for non-sorted endothelial cells, which is again consistent with previous studies[26]. Several genes and pathways have been previously described to exhibit increased expression in sprouting cells, including Notch signaling[40], VEGF receptors[41], various adhesion molecules [42] and cell surface receptors [43,7]. However, in our study, VEGFR1 and VEGFR2 were in the group of 54 genes that displayed similar levels of expression in the sprouting cells and non-sorted endothelial cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the profile of cytokines secreted by the sprouting cells was very similar to that observed for non-sorted endothelial cells, which is again consistent with previous studies[26]. Several genes and pathways have been previously described to exhibit increased expression in sprouting cells, including Notch signaling[40], VEGF receptors[41], various adhesion molecules [42] and cell surface receptors [43,7]. However, in our study, VEGFR1 and VEGFR2 were in the group of 54 genes that displayed similar levels of expression in the sprouting cells and non-sorted endothelial cells.…”
Section: Discussionsupporting
confidence: 88%
“…Endothelial tip cells are the leading cells of a sprout, and are highly polarized and migratory, minimally proliferative, and display numerous extended filopodia[6]. Endothelial stalk cells follow the tip cells, and are characterized by fewer filopodia, higher proliferative capacity and lumen formation and coordination[7]. Although there exists plasticity and reversibility between these phenotypes during sprouting[8], very little is known about whether cells that participate in formation of new sprouts, as compared to those that do not, were previously committed to a more angiogenic phenotype, or if this is a stochastic process.…”
Section: Introductionmentioning
confidence: 99%
“…Blancas et al reported a chemically defined protocol using growth factors, including VEGF-A and BMP-4, along with ECMs such as fibronectin. 6 Wu et al employed not only soluble inducing factors of CHIR-99021and VEGF-A, but also the anti-absorptive agent polyvinyl alcohol to preferentially detach non-endothelial lineages, resulting in high yields of iPSC-ECs. 54 Whereas high-efficiency differentiation protocols such as that from Wu et al 54 might mask the potential benefit of 3D scaffolds, in this study we employed a differentiation protocol 45 that, in our hands, yielded ~20% efficiency of CD31 + iPSC-ECs in conventional tissue culture dishes, and thereby allow for the possibility of observing an enhancement in differentiation in 3D scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis proposed Hox genes as a key driver determinant of the differentiation variability. Other works have shown that extracellular matrix coating, serum and seeding density can also affect differentiation of pluripotent cells to the endothelial lineage 41, 42 .…”
Section: Challenges For Ipsc Mediated Modeling Of Insulin Resistance mentioning
confidence: 99%